Daya Terima Cookies Dengan Substitusi Tepung Kacang Merah Dan Penambahan Tepung Daun Kelor Sebagai Snack Sehat Untuk Remaja Putri Anemia Defisiensi Besi - Annisa Fajar Aulia; Asrul Bahar; Amalia Ruhana; Noor Rohmah Mayasari (Jurnal Ilmu Kesehatan dan Gizi, 2024)
The growth of new innovations makes snacks rich in iron and protein in the form of cookies using red bean flour substitution and the addition of moringa flour. This study aims to determine the effect of red bean flour substitution, the addition of moringa flour, and the interaction of the two factors on the acceptability of cookies (color, aroma, taste, and crispness), as well as the protein and iron content contained in the best cookie formula. The study was conducted in Surabaya on adolescent girls. This type of research is experimental with a two-factor randomized complete block design (RAL). The study used descriptive analysis of nutritional content (protein and iron) obtained from the laboratory. Acceptability will be tested parametric statistics using Two-ways Anova statistics. The results showed that red bean flour affects the color and crispness of cookies (<0.05); Moringa leaf flour affects the color, aroma and crispness (<0.05); the interaction between the two only affects the crispness (<0.05); and protein and iron in accordance with SNI dan Nutritional Adequancy Rates.